Hubungan Kepatuhan Imunisasi Tetanus Toksoid Pada Calon Pengantin Wanita Di Wilayah Kerja KUA Watang Sawitto Pinrang (Window of Public Health Journal, 2026)
Tetanus toxoid (TT) immunization is one of the tetanus prevention efforts for prospective brides that plays an important role in protecting the health of mothers and babies in the future. Low compliance with TT immunization can increase the risk of maternal and neonatal tetanus. This study aims to determine factors related to tetanus toxoid immunization compliance among prospective brides in the working area of the Office of Religious Affairs (KUA) in Watang Sawitto District, Pinrang Regency. This study used a quantitative, cross-sectional design. The study population comprised all prospective brides in the working area of the KUA Watang Sawitto District, Pinrang Regency. The research sample was selected using a purposive sampling technique. Data analysis was carried out univariately and bivariately using the Chi-Square test with a 95% confidence level (α = 0.05). The results showed significant relationships between knowledge (p = 0.002), attitude (p = 0.000), motivation (p = 0.000), and family support (p = 0.000) and tetanus toxoid immunization compliance among prospective brides. This study concluded that increasing health education can build confidence and motivate prospective brides to comply with immunization recommendations, emphasizing the importance of targeted health communication.